Electrochemical scrutinizing techniques on initial development of pseudomonas aeruginosa strain (PAO1) biofilms - Foo, Yu Hao (2018)
Bacteria are ubiquitous, forming biofilms on nearly any surface in an aqueous environment. The accumulation of biofilms on the surface of industrial equipment is natural yet often detrimental. In clinical settings, biofilms forming on medical implants pose health risks for patients with compromised immune systems; biofilms release a variety of virulence factors and are extremely resistant to antibiotics. Eradicating biofilms, especially mature ones, is a challenge. Early detection of biofouling is crucial in the monitoring and controlling of biofilm formation, allowing for application of more potent strategies to eliminate biofilms. There remains a need for precise on-line monitoring techniques that are wieldy and cost effective, to detect early biofilm establishment in real time. We investigated a real-time electrochemical technique that allows the monitoring of bacterial adhesion and early biofilm growth of the bacteria strain Pseudomonas Aeruginosa (PAO1) using Potentiostatic Electrochemical Impedance Spectroscopy (PEIS), and repetitive Cyclic Voltammetry (CV) to observe charge transfer resistance (Rct) and biofilm capacitance (QBiofilm) or double layer capacitance. The effect of growth time substrate (0 – 96h), electrode geometry, and concentrations of the mediator Potassium Ferricyanide (0, 1, 5, 10mM) were investigated. Effects of external mechanical stimulation on the biofilm using ultrasound were also studied in a separate experiment. PEIS results show that the value of the charge transfer resistance (Rct) decreased while biofilm capacitance or double layer capacitance increased with accumulative cell density supported with absorbance data from Crystal Violet Staining. These results provided insight into the necessary protocols for scrutinising the early development of PAO1 using electrochemical techniques.